Chemical Migration and Emulsification of Surfactant-Polymer Flooding - Jierui Li; Weidong Liu; Guangzhi Liao; Linghui Sun; Sunan Cong; Ruixuan Jia (Journal of Chemistry)
With a long sand-packed core with multiple sample points, a laboratory surfactant-polymer flooding experiment was performed to study the emulsification mechanism, chemical migration mechanism, and the chromatographic separation of surfactant-polymer flooding system. After water flooding, the surfactant-polymer flooding with an emulsified system enhances oil recovery by 17.88%. The water cut of produced fluid began to decrease at the injection of 0.4 pore volume (PV) surfactant-polymer slug and got the minimum at 1.2 PV. During the surfactant-polymer flooding process, the loss of polymer is smaller than that of surfactant, the dimensionless breakthrough time of polymer is 1.092 while that of surfactant is 1.308, and the dimensionless equal concentration distance of the chemical is 0.65. During surfactant-polymer flooding, the concentration of surfactant controls the formation of the emulsion. From 50 cm to 600 cm, as the migration distance increases, the concentration of surfactant decreases, and the emulsification strength and duration decrease gradually. With the formation of emulsion, the viscosity of the emulsion is relatively stable, which is beneficial to enhanced oil recovery. With the shear of reservoirs and migration of surfactant-polymer slug, the emulsion is formed to improve the swept volume and sweep efficiency and enhance oil recovery.